Arte, cultura o entretenimiento en el cine: ¿Qué modelo cinematográfico prefieren los espectadores para tomar la decisión de asistir a ver una película? (Arts, culture or entertainment in motion pictures: What film model do spectators prefer on the decision making to watch a movie?) - Lozano Treviño, David Fernando; Treviño Ayala, María Eloísa (Facultad de Contaduría Pública y Administración, 2014)
Abstract. This research paper has as main purpose to determine which film model is more convenient for the Mexican film production organizations in the search of increasing the possibilities of spectators to attend and watch their movies. The character that the films have as popular and academic arts and the elements that compose it is analyzed. We study the way in which motion pictures work as cultural tools. We highlight the importance of movies as an entertainment product and how this aspect impacts in the consumption of movie tickets in the box office. Lozano-Barragan syndrome is detailed and how filmmakers can suffer this artistic, marketing and economic discomfort. Finally, we make some linear regressions to determine the impact that the film models inclusions have on increasing the possibilities of spectators attending to the films.